The Comparison between German and Vietnamese Cultural Standards - Luong Minh Nguyet (Nusantara Science and Technology Proceedings)
In today's world of globalization, all countries place a particular value on reinforcing development cooperation. Vietnam and Germany are no exception. However, with increasing intercultural encounters, conflicts arising from cultural differences also occur more frequently. Therefore, there is a need to better prepare the citizens from Vietnam and Germany for their future work in each other’s country. This paper will study the German and Vietnamese cultural standards and their effects on the work behavior of people from the respective cultures. For this purpose, German and Vietnamese culture are first compared on the basis of the cultural standard concept. An empirical study using qualitative research methods will also be carried out, in which the experiences of daily working life in the other country of several Germans and Vietnamese as well as their solutions for similar situations are analyzed. The aim of this analysis is to find out how cultural standards affect their behaviors at work, and what conflicts may arise in the process. The results of this study should provide important knowledge in avoiding conflicts during the cooperation as far as possible.